Tradisi Ruwat Bumi Dan Harmonisasi Umat Beragama di Desa Ambarawa Barat Kecamatan Ambarawa Kabupaten Pringsewu - Putri, Ayu Melinda; Rosana , Ellya; Salim, Luthfi (Prodi Sosiologi Universitas Mataram, 2024)
This research aims to examine in depth the ruwat bumi tradition in West Ambarawa village as a form of religious harmony becoming a social norm that is adhered to by all members of the community. The Ruwat Bumi tradition, which is a traditional Javanese ceremony which aims to cleanse the village so that the harvest is abundant, the livestock have lots of children, the merchandise sells well and is kept away from various kinds of disasters is a tradition that has been passed down from ancestors from generation to generation, which turns out to be able to form harmony between people. religious. Community adherence to the Ruwat Bumi tradition makes this tradition a social norm that regulates how people act and behave. The researcher formulated several problem formulations, namely: How can the Ruwat Bumi tradition form the harmonization of religious communities in the village of West Ambarawa? The methodology in this journal uses descriptive qualitative research methods. The data collection method uses three methods, namely observation, interviews and documentation methods. In determining informants to be interviewed, the researcher used a purposive sampling technique where the researcher selected relevant informants to be interviewed according to related themes. The results of the research are that the Ruwat Bumi tradition in forming religious harmony takes several forms (1) cooperation (2) recognition of differences (3) similarities in heterogeneity (4) feelings of mutual belonging (5) consistent social norms that do not change . This is the rule for good behavior in the social life of the people of West Ambarawa village. The application of the norms that exist in the Ruwat Bumi tradition is a big asset for a harmonious and peaceful religious life.